Energy turnover at the Race Across AMerica (RAAM) - a case report - Knechtle, B.; Enggist, A.; Jehle, T. (International Journal of Sports Medicine, 2005)
We report about energy intake and energy expenditure in an official finisher of the Race Across AMerica (RAAM) in 2003. Energy intake from nutrition was continuously recorded. Energy expenditure was measured by continuous heart rate recording with a portable heart rate monitor POLAR® S710 to estimate energy expenditure during physical activity. Our athlete (33 years, 179 cm,7 3 kg, VO2max 60ml·min-1· kg-1,lactate threshold at 77% VO2max) finished the 4701-km cycling race with altitude differences amounting to 25826 meters in 9 days 16 hours and 45 minutes in 4th place. He completed 470 ± 72.9 km (372-541 km) per day with 2582 ± 1576 (683-5047) meters of altitude. During the whole race,he expended a total energy of 179650 kcal with 17965 ± 2165 (15100-23280) kcal per day. Total energy intake was 96124 kcal with an average of 9612 ± 1500 (7513-12735) kcal per day. Of total ingested calories,75.2 % derived from carbohydrates,16.2% from fat, and 8.6% from protein. He ingested an energy of 9612 ± 1550 (7513-12735) kcal daily, consisting of 1814 ± 310 (1336-2354) g of carbohydrates,1 72 ± 47 (88-251) g of fat,and 207 ± 52 (128-286) g of protein. The average daily energy deficiency amounted to 8352 ± 2523 (4425-13631) kcal. A total deficiency of 83526 kcal resulted after the race while the athlete lost 5 kg of body weight. These results provide data about energy intake and energy expenditure in the RAAM for future athletes,nutritionists and coaches. Further investigation should be performed in order to determine whether either muscle mass or body fat will be lost in extreme endurance cycling.